The Popular Ergogenic Substances in Sport and Physical Activity - Katarzyna Świtała (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2023)
Few supplements have a scientifically proven ergogenic effects of improving exercise capacity and/or physical performance in sport. The athletes require specialised nutrition, including precisely good quality supplementation, i.e. scientifically tested. Nowadays, more and more athletes use nutritional supplementation to improve their sporting performance both at the elite and non-elite levels. In this review, ergogenic substances such as the β-alanine, caffeine, creatine monohydrate, creatine malate, sodium bicarbonate were analysed among athletes/active people from an exercise and health capacity perspective. The aim of this review is to analyse the efficacy, mechanisms of action, dosage, side effects of the selected ergogenic substances, among athletes involved in physical effort/specific sport disciplines. Furthermore, the article will show the benefits of using these supplements in terms of health as well as improvement of exercise capacity among athletes.